Active galactic nucleus X-ray luminosity function and absorption function in the Early Universe (3 [less than or approximately equal] z [less than or approximately equal] 6) - Pouliasis, Ektoras; Ruiz, A.; Georgantopoulos, I.; Vito, F.; Gilli, R.; Vignali, C.; Ueda, Y.; Koulouridis, E.; Akiyama, M.; Marchesi, S.; Laloux, B.; Nagao, T.; et al. (Astronomy and astrophysics, 2024)
The X-ray luminosity function (XLF) of active galactic nuclei (AGN) offers a robust tool to study the evolution and the growth of the supermassive black-hole population over cosmic time. Owing to the limited area probed by X-ray surveys, optical surveys are routinely used to probe the accretion in the high-redshift Universe z ≥ 3. However, optical surveys may be incomplete because they are strongly affected by dust redenning. In this work we derive the XLF and its evolution at high redshifts (z ≥ 3) using a large sample of AGN selected in different fields with various areas and depths covering a wide range of luminosities. Additionally, we put the tightest yet constraints on the absorption function in this redshift regime. In particular, we used more than 600 soft X-ray selected (0.5 − 2 keV) high-z sources in the Chandra deep fields, the Chandra COSMOS Legacy survey, and the XMM-XXL northern field. We derived the X-ray spectral properties for all sources via spectral fitting, using a consistent technique and model. To model the parametric form of the XLF and the absorption function, we used a Bayesian methodology, allowing us to correctly propagate the uncertainties for the observed X-ray properties of our sources and also the absorption effects. The evolution of XLF is in agreement with a pure density evolution model similar to what is witnessed at optical wavelengths, although a luminosity-dependent density evolution model cannot be securely ruled out. A large fraction (∼60%) of our sources are absorbed by column densities of NH ≥ 10 23 cm−2, while ∼17% of the sources are Compton-Thick. Our results favour a scenario where both the interstellar medium of the host and the AGN torus contribute to the obscuration. The derived black hole accretion rate density is roughly in agreement with the large-scale cosmological hydrodynamical simulations, if one takes into account the results that the X-ray AGN are hosted by massive galaxies, while it differs from that derived using JWST data. The latter could be due to the differences in the AGN and host-galaxy properties.